Diseño de una propuesta para el mejoramiento en la gestión de la cadena de suministro en el proceso de recolecta y llegada de aves a la planta procesadora de la Empresa Pollo Rey, en el Coyol de Alajuela - León-Vargas, María José (Instituto Tecnológico de Costa Rica, 2017)
The goal in this project is to develop a proposal for the improvement of the supply chain in the stages of caught, transport and arrival of chicken to the plant in order to minimize any damages that could happen to the cages that are used to carry the birds that will be processed at Pollo Rey Company, which is located in El Coyol of Alajuela, Costa Rica. The document presents the application of the Six Sigma methodology as a tool for the continuous improvement of processes. In this study, the definition, measurement and analysis steps will be used. In the matter of achieving the objectives of the search, this document shows the methodology that was executed for accomplishing them and also the tools that were used to establish the actions that cause damages in the cages. There is also documentation that was used as a source of valuable information that was consulted during the execution of the project. In here you will also find the results of the investigation, such as the absence of and adequate spare parts stock or the lack of information of the workers about the guidelines to execute operations where the cages are used. The detection of the causes of damages in the cages allow the development of an improvement proposal for the processes that were reviewed in this investigation. That will later be given to the company so they can have a guide for taking action in order to make their commercial activities more profitable.
Proyecto de Graduación (Licenciatura en Ingeniería en Agronegocios) Instituto Tecnológico de Costa Rica, Escuela de Agronegocios, 2017.
Keywords: Transporte; Propuestas; Cadena de suministo; Procesamiento; Jaulas; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Product science::Food science